Early muscle hypotonia as a potential marker for autism spectrum disorder: a systematic review - Zhang, Ting; Wang, Jinying; Cao, Zhenkun; Ma, Yuhan; Lv, Zhihai (Frontiers in Psychiatry, 2025)
BackgroundThe diagnosis of ASD has increased globally owing to the expansion of diagnostic criteria, increased awareness, and improvement in symptom identification. However, the diagnosis of ASD in young or neurodivergent people remains challenging and requires the investigation of new early indications.ObjectivesIn this review, we examined the correlation between early hypotonia (including motor difficulties) and ASD, evaluating the potential of hypotonia as an early biomarker and screening instrument.MethodsUsing the PRISMA criteria (PROSPERO: CRD42024626398), we searched PubMed, Embase, Cochrane Library, and Web of Science without any constraints on date or language. The inclusion criteria were derived from studies on children aged 0–6 years that investigated hypotonia (e.g., motor impairments or head lag) in connection with ASD diagnosis or characteristics. The eligible studies were prospective cohort, case-control, and retrospective video-analysis studies. Two researchers independently collected and evaluated the data.ResultsTwenty-four studies (prospective cohort, case-control, or video analyses) were included in this review.The participants were aged 2 months to 6 years and included infant siblings of autistic children (a cohort with elevated likelihood of an autism diagnosis), children with familial ASD, and individuals from the general population.The research showed a consistent association of hypotonia and motor difficulties with ASD, despite variations in assessment methodologies, such as standardized motor measures and clinical evaluations. However, despite methodological heterogeneity, cumulative evidence supported the potential of hypotonia as an early ASD biomarker.ConclusionHypotonia and related motor differences may serve as practical screening indicators of increased likelihood of a later autism diagnosis. Identifying these signs can prompt earlier referral and support. While the findings are promising, further research is needed to standardize assessment protocols and validate clinical utility. Interdisciplinary collaboration may facilitate early detection, enhancing long-term outcomes through timely assistance.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD42024626398.